A Direct Electrochemical H2S Sensor Based on Ti3C2Tx MXene. Issue 19 (16th September 2021) - Liu, Xinran; He, Liang; Li, Ping; Li, Xinqi; Zhang, Pandong
Abstract: The layered structure of two‐dimensional transition metal carbon/nitride and its excellent physical and chemical properties make it a major research hotspot in the field of sensing. Meanwhile, characteristics such as good biocompatibility and hydrophilicity make this type of material a good potential biological sensing material. In this work, a graphene‐like structure composed of multilayer Ti3 C2 Tx MXene was successfully synthesized by a simple hydrogen fluoride etching method, and an attempt was made to use it for non‐enzymatic H2 S electrochemical sensing. The electrochemical test results show that the modified Ti3 C2 Tx MXene/GCE has a high sensitivity (0.587 μA μM −1 cm −2 ) for the detection of trace H2 S. At the same time, it shows a low detection limit (16.0 nM) and a wide detection range (100 nM–300 μM). The result provides a new research direction for H2 S electrochemical sensing, as well as a new platform for MXene materials in biological sensing. Abstract : A multilayer Ti3 C2 Tx MXene is prepared by a hydrofluoric acid etching method for electrochemical H2 S sensing. Assembled with a glassy carbon electrode to form a sensing element, this material exhibits a low detection limit and a high sensitivity for hydrogen sulfide electrochemical sensing. The results are unaffected by testing in complex serum samples.